Dampak Digital Marketing terhadap Minat Beli Konsumen di Toko Karyatama Lubuklinggau - Lingga, Riswandha Imawan; Syafitri, Anggia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Advances in the digital era mean that people can get everything just by their hand. Technological advances also provide significant changes to the business world. Because like it or not, business actors have to adapt to business digitalization which is not limited to place or time. Business digitalization itself is a process that changes communication, interaction and all benefits in business to digital. Through the implementation of business digitalization, business actors are switching from conventional systems to virtual ones. From the innovations that have been carried out by the Karyatama in this digital era, researchers are interested in studying whether the digitalization that has been carried out has an impact on increasing consumer buying interest at the Karyatama Lubuklinggau. The type of research used in this research is descriptive research, namely research conducted to determine the impact of digital marketing on increasing consumer buying interest at the Karyatama Lubuklinggau